Daya Patah Dan Daya Terima Flakes Jagung Yang Disubtitusi Tepung Jantung Pisang - Kurniasih, Angit; , Siti Zulaekah, A., M.Si; , Rusdin Rauf, S.TP., MP (2016)
Introduction : Flakes are prepared products which are favored and quick in the preparation. The raw material used in flakes preparation is corn. The addition of banana flower flour in flakes is to enhance it's fiber. Purpose : The purpose of the research was to determine the effect of banana flower flour substitution on corn flakes to the brittleness and acceptance of the flakes Method : The research method was completely randomized design with 4 treatments of banana flower flour substitution ie 0% (control), 15%, 20%, 25%. The analysis of brittleness was using Texture Analyzer CT-03 Brookfield. Data was analysed of one way statistical (ANOVA) and followed by Duncan Multiple Range Test (DMRT) with a 95% significance level. Result : The results showed that banana flower flour substitution did not affect of the brittle power of flakes. The highest and lowest of brittleness gave by substitution of 15% and 20%, respectively based on 4 substitution treatments, the best acceptance of flakes displayed by substituted of 0%, followed by 15%. Conclusion : There was no effect of the banana flower flour substituion to the brittleness of flakes. the acceptance of banana flower flour substitution affect on color, aroma, taste and overall, but did not affect to the texture of flakes. Suggestion : It is necessary to analyse proximate composition and fiber content in corn flakes.